2016
DOI: 10.3126/ijasbt.v4i1.14574
|View full text |Cite
|
Sign up to set email alerts
|

Bacillus Spp. Amylase: Production, Isolation, Characterisation and Its Application

Abstract: Amylase is one of the leading enzymes used in industry from decades. The preliminary function of this enzyme is the hydrolysis of the starch molecule into glucose units and oligosaccharides. Amylases have spectacular application in broad spectrum of industries such as food, detergent, pharmaceutical and fermentation industries. Among different type of amylases α-amylase is in utmost demand because of its striking features. This particular enzyme is a good substitute over the chemicals catalyst used in industri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…This pH range shows the versatility of the enzyme for several process conditions. These optima observed indicated the enzyme was at its satisfactory conformation (Sachdev et al, 2016). Kumar and Duhan (2011) and Alva et al (2007) reported similar pH ranges of (4.2 and 8.4) and (5.8 and 9) for Aspergillus niger MTCC -104 and Aspergillus sp JG112 amylases respectively.…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…This pH range shows the versatility of the enzyme for several process conditions. These optima observed indicated the enzyme was at its satisfactory conformation (Sachdev et al, 2016). Kumar and Duhan (2011) and Alva et al (2007) reported similar pH ranges of (4.2 and 8.4) and (5.8 and 9) for Aspergillus niger MTCC -104 and Aspergillus sp JG112 amylases respectively.…”
Section: Resultsmentioning
confidence: 74%
“…The effect of temperature on the activity of amylase showed that the enzyme activity increased progressively with an increase in temperature from 30 o C (16.73 U/ml-min) to a maximum of 28.41 U/ml-min at 60 o C (Figure 2). Reduction in amylase activities was observed at temperatures below 60 o C. The decrease in amylase activity may be attributed to the disruption of the secondary, tertiary and quaternary bonds of the amylase enzyme (Sachdev et al, 2016;Schokker et al, 1998). An optimum temperature of 70 o C was recorded for an amylase produced by Aspergillus niger on yam peels (Uguru et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Amylases useful for various industrial applications were previously isolated from Bacillus strains that can utilize agro-waste carbon sources and showed activity at wide range of temperature and pH [15]. In this study, we have identified two amylase producing bacterial strains, B. megaterium and E. auranticum from enriched soil.…”
Section: Discussionmentioning
confidence: 99%
“…Bacillus spp. bacteria, commonly isolated from fermented maize products, are beneficial as well for the fermentation process due to the production of amylase [90], and particularly of α-amylases, which convert starch to glucose for microorganisms lacking in these enzymes, such as S. cerevisiae [91].…”
Section: Production Of Amylolytic Enzymesmentioning
confidence: 99%